2018
DOI: 10.1103/physrevb.98.115148
|View full text |Cite
|
Sign up to set email alerts
|

The generalized Kadanoff-Baym ansatz with initial correlations

Abstract: Within the non-equilibrium Green's function (NEGF) formalism, the Generalized Kadanoff-Baym Ansatz (GKBA) has stood out as a computationally cheap method to investigate the dynamics of interacting quantum systems driven out of equilibrium. Current implementations of the NEGF-GKBA, however, suffer from a drawback: real-time simulations require noncorrelated states as initial states. Consequently, initial correlations must be built up through an adiabatic switching of the interaction before turning on any extern… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 29 publications
(64 reference statements)
1
59
0
Order By: Relevance
“…In Eq. (8) this gives rise to an additional homogeneous solution that leads to an additional collision integral in the time-diagonal KBE (2), in agreement with recent results [20,21].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…In Eq. (8) this gives rise to an additional homogeneous solution that leads to an additional collision integral in the time-diagonal KBE (2), in agreement with recent results [20,21].…”
supporting
confidence: 90%
“…This behavior can be relieved by applying the Generalized Kadanoff-Baym ansatz (GKBA) [16,17] which reduces the dynamics of the NEGF, G(t, t ), to propagation along the time diagonal, t = t . It could be demonstrated that, indeed, the expected improvement of the scaling, N 3 t → N 2 t (in the following we will use the number of discretization time steps N t = T /∆t), can be achieved in practice for the selfenergy in second order Born approximation (SOA) [18,19] where initial correlation effects can be treated even more efficiently [20,21]. It could further be shown that this approximation, in many cases, does not lead to a loss of accuracy [10,15,22].…”
mentioning
confidence: 99%
“…In addition, many other similar multi-index operations, such as evaluating the initial correlations collision integral in Ref. [53], might become computationally more accessible by using the tensorcontraction representations. The presented simulations in selected molecular systems provided concrete evidence of the accuracy and applicability of the tensor-contraction operations.…”
Section: Resultsmentioning
confidence: 99%
“…The correlated initial state therefore needs to be prepared by starting with an uncorrelated (or HF) system and slowly switching on the interaction (adiabatic switching procedure) [25,36,48,51]. However, the inclusion of the initial correlations has been shown to be possible also within GKBA [52][53][54].…”
Section: )mentioning
confidence: 99%
“…The knowledge of G gives access to all single-particle quantities (e.g., density, momentum distribution, density of states). For an interacting system the SPGF can be found by solving either the Kadanoff-Baym equations [18,29,31,32], the Dyson equation [33,34], or other equivalent techniques [35][36][37][38][39]. A crucial point is the choice of a selfenergy, which is typically a functional of the SPGF itself.…”
Section: Nonequilibrium Green's-function Approachmentioning
confidence: 99%